Pressure based control for a variable speed diesel engine driven pump controller - Muhammad Arieffuddin, Mohd Jamil; Fadhlur Rahman, Mohd Romlay; Khairul Fikri, Muhammad; Shamsudin, Abdul Samat; Ismayuzri, Ishak (Penerbit UMP, 2021)
Chemical cleaning is a process that utilizes chemical as a cleaning medium to remove unwanted contaminants. The chemical cleaning process may involve with the use of pump to circulate the chemical during cleaning process. The pump for the cleaning process can be driven by electrical or internal combustion engine. This paper presents the development of a variable speed diesel engine driven pump controller for chemical cleaning application. The controller utilize proportional control method as the control scheme. The variable speed diesel engine driven pump system includes a diesel engine coupled with centifugal pump, a controller, pressure sensor, and battery powerpacks. All the components are mounted on a skid platform for the ease of use as a system. Proportional control method were used in order to get the critical gain parameter to compute PID parameter gains using Ziegler Nichols tuning method